Value of psychological counseling for trainees exposed to the death of a patient in emergency and resuscitation departments. (1st June 2022) - Betbout, I.; Amemou, B.; Ben Haouala, A.; Ben Arbia, Y.; Khadhrawi, I.; Zaafrane, F.; Mhalla, A.; Gaha, L.
Abstract : Introduction: Trainee emergency and resuscitation technicians are not prepared during their academic training to deal with their psychological reactions to the death of a patient, we wanted to describe their feelings and understand the aggravating factors and highlight the need for intervention. Objectives: Our study aims to describe the psychological reactions of traineesexposed to the death of a patient on the internship grounds and to demonstrate the usefulness of specific psychological counseling Methods: It is a prospective interventional study carried out with 2nd and 3rd-year students of the emergency and resuscitation section, our collection was done using a self-administered questionnaire with a validated PDI scale before the training, and a satisfaction questionnaire with the same scale after the training. Results: Our population isyoung, with an averageage of 20.05 years, and ispredominantlyfemale, with a sex ratio of 0.12. Eighty-seven percent of the population statedthatthey were not prepared to deal with their feelings about the death of a patient, and thiseventharmed the quality of care for 68% of the students. According to the scores of the PDI scale in pre-training 77.33% of the students are at risk of developing PTSD, this percentage decreases to 30.67% according to the same scale in post-training. Conclusions: it is important to take into consideration the suffering of traineesexposed to traumaticevents such as the death of patients and to prepare them psychologically to deal with these situations Disclosure: No significant relationships.